Corneal Collagen Crosslinking for Post‐LASIK Ectasia: An Australian Study. Issue 3 (May 2017) - Tong, Jessica Y.; Viswanathan, Deepa; Hodge, Christopher; Sutton, Gerard; Chan, Colin; Males, John J.
Abstract : Purpose: : Post laser‐assisted in situ keratomileusis (LASIK) ectasia is a rare and unpredictable complication after LASIK. Corneal collagen crosslinking (CXL) has emerged as a promising technique to address this complication. Our study evaluates the long‐term efficacy of CXL for post‐LASIK ectasia in an Australian setting. Design: : Retrospective review of post‐LASIK ectasia patients referred to and treated at 3 corneal refractive surgery institutions in Sydney, Australia. Methods: : Eleven patients (14 eyes; mean age, 39.7 ± 12.6 years) underwent epithelium‐off CXL with follow‐up ranging from 12‐78 months. Best spectacle‐corrected visual acuity (BSCVA), simulated keratometry, corneal topography indices, and higher‐order aberrations (HOAs) [mean ± standard error of the mean (SEM)] were measured with a rotating Scheimpflug camera (Pentacam, Oculus). Comparisons between baseline measurements and postoperative outcomes were performed using paired t test analysis. Results: : At last follow‐up, BSCVA improved significantly by 0.2 ± 0.06 logMAR ( P = 0.01), and 12 of 14 eyes showed no keratometric deterioration. Of the corneal topography indices, index of height asymmetry showed a trend toward a significant improvement ( P = 0.05). There was no progression of corneal HOAs. Central corneal thickness was not significantly altered ( P = 0.6). No major postoperative complications were observed. Conclusions: : In the Australian setting, CXL has proven effective at stabilizing the progression of post‐LASIK ectasia, inducing corneal regularity, and improving visual acuity.